The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1055/a-1332-6902
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with per-rectal endoscopic myotomy for Hirschsprung’s disease: medium and long term outcomes of the first case series of a novel third-space endoscopy procedure

Abstract: Introduction Hirschsprung’s disease (HSCR) is congenital aganglionosis affecting hindgut and presents with constipation. Surgical pull-through is current standard but has morbidity. Per-rectal endoscopic myotomy (PREM) is a novel third space endoscopy technique for treating SS-HSCR. Methods Retrospective series of SS-HSCR patients diagnosed on history, contrast enema, rectal biopsies, anorectal manometry and treated by PREM. Aganglionic segment mapped pre-PREM. PREM performed using third space endoscopy pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Despite the delay, our results demonstrate excellent functional outcomes. The median age of patients in our study was 4 years and not 7.5 years as stated by the authors (Table 1 s) 1 .…”
supporting
confidence: 47%
See 1 more Smart Citation
“…Despite the delay, our results demonstrate excellent functional outcomes. The median age of patients in our study was 4 years and not 7.5 years as stated by the authors (Table 1 s) 1 .…”
supporting
confidence: 47%
“…
We thank Dr. Chung and colleagues for their comments on our study [1]. The following are our responses to the queries raised.
…”
mentioning
confidence: 99%
“…65 Subsequently, the authors reported the outcomes of PREM in nine patients with short-segment HD. 67 The mean age of patients was 7.5 ± 5.2 years and the average length of aganglionic segment was 6.3 cm. The procedure was successfully performed in all the cases with a mean operative time of 96.1 minutes.…”
Section: Per-rectal Endoscopic Myotomymentioning
confidence: 97%
“…64 Recently, endoscopic management (utilizing the principles of third space endoscopy) has shown encouraging results in these cases. [65][66][67] The technique of per-rectal endoscopic myotomy (PREM) as described by Bapaye and colleagues is discussed here. 65 The first and foremost step involves mapping of aganglionic segment by analyzing serial biopsies obtained using the technique of band assisted endoscopic mucosal resection (EMR) described by Nabi and colleagues.…”
Section: Per-rectal Endoscopic Myotomymentioning
confidence: 99%
“…We read with great interest the article by Bapaye et al who described per-rectal endoscopic myotomy as a treatment for Hirschsprungʼs disease (HSCR) 1 . We congratulate the authors on their novel technique but have concerns regarding patient selection, outcome assessment, and the long-term results reported in this study.…”
mentioning
confidence: 99%